Dual Adjuvant‐Loaded Peptide Antigen Self‐Assembly Potentiates Dendritic Cell‐Mediated Tumor Immunotherapy - Kim, Jaehyun; Kang, Seyoung; Kim, Jisu; Yong, Seok‐Beom; Lahiji, Shayan Fakhraei; Kim, Yong‐Hee (Advanced science, 2024)
Clinical translation of current cancer vaccine research has been hampered by limited antitumor immune responses due to inefficient antigen delivery and presentation, suboptimal DC and T cell activation. Biomaterial‐based nanovaccine offers targeted antigen delivery, protection from degradation in vivo, and prolonged tumor therapeutic efficacy. This study introduces a lipid‐coated deoxycholic acid‐survivin nanoassembly (DA‐L‐DSA). Survivin, overexpressed in several cancer cells and involved in cancer cell growth and immune evasion, is selected as a tumor‐associated antigen. An major histocompatibility complex class I binding epitope of survivin is engineered into the nanoassembly. R848, TLR 7/8 agonist, and SD‐208, TGF‐beta receptor1 kinase inhibitor, are coencapsulated into the nanoassembly as potent adjuvants to boost DC maturation and enhance antigen presentation. The DA‐L‐DSA effectively stimulates the maturation of dendritic cells, migrates into lymph nodes, and enhances T‐cell activation and Th1 response. A substantial influx of cytotoxic T lymphocytes into primary tumors is observed in a murine melanoma model and demonstrates anti‐metastatic effects in a spontaneous breast cancer metastasis model. Furthermore, DA‐L‐DSA exhibits a remarkable synergistic effect in the combination therapy with immune checkpoint inhibitors alleviating immunosuppressive tumor microenvironment. Taken together, these findings suggest DA‐L‐DSA as a promising immuno‐therapeutic platform that could be applicable to diverse intractable cancers. This study demonstrates the efficacy of dendritic cell‐mediated anticancer immunotherapy in allograft melanoma models and metastatic breast cancer models by producing major histocompatibility complex (MHC) I binding peptide epitopes of survivin proteins expressed in various cancers in the form of self‐assembled nanostructures with dual adjuvants.